The future of fallout, and other episodes in radioactive world-making - Masco, Joseph 1964- (Duke University Press, 2021)
In The Future of Fallout, and Other Episodes in Radioactive World-Making Joseph Masco examines the strange American intimacy with and commitment to existential danger. Tracking the simultaneous production of nuclear emergency and climate disruption since 1945, he focuses on the psychosocial accommodations as well as the technological revolutions that have produced these linked planetary-scale disasters. Masco assesses the memory practices, visual culture, concepts of danger, and toxic practices that, in combination, have generated a U.S. national security culture that promises ever more safety and comfort in everyday life but does so only by generating and deferring a vast range of violences into the collective future. Interrogating how this existential lag (i.e., the material and conceptual fallout of the twentieth century in the form of nuclear weapons and petrochemical capitalism) informs life in the twenty-first century, Masco identifies key moments where other futures were still possible and seeks to activate an alternative, postnational security, political imaginary in support of collective life today
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Emergency management; National security; Nuclear warfare; Terrorism -- Prevention; Threats of violence; World politics -- 21st century; Atomkriegsgefahr; Psychosoziale Situation; USA